Yahoo Web Search

  1. ... - 3n - 1) P(1): 1² = 1/2(1)[6(1)² - 3(1) - 1] LHS = 1 RHS = 1 Proposition P(1) is confirmed...

    3 Answers · Science & Mathematics · 20/01/2021

  2. ... as x² = (2.3 - x)*1.19 * 10 ^-7. Then put all on the LHS . Then expand. Notice now that you have a quadratic of the form ...

    3 Answers · Science & Mathematics · 17/01/2021

  3. RHS = 2tan(2x)sin²(x) = tan(2x){1 - [1 - 2sin²(x)]} = tan(2x)[1 - cos(2x)] = tan(2x) - tan(2x)cos(2x) = tan(2x) - sin(2x) = LHS

    2 Answers · Science & Mathematics · 15/01/2021

  4. ...3 terms to evaluate: (3-6)x + (4-6)x + (5-6)x = 72. Simply the LHS . What does it give? [ = -6x ] Then, solving for x ...

    2 Answers · Science & Mathematics · 11/11/2020

  5. Yep, ordinary algebra.  Divide both sides by the same value and the equation remains balanced.  The LHS still = the RHS.  So divide away and enjoy.

    3 Answers · Science & Mathematics · 19/08/2020

  6. RHS = cot²(x)[csc³(x) - csc(x)] = cot²(x)csc(x)[csc²(x) - 1] = cot²(x)csc(x)cot²(x) = cot⁴(x)csc(x) = LHS

    1 Answers · Science & Mathematics · 09/05/2020

  7. ... + Fr = mh''.  Use the correct signs for the LHS terms. Fg is a constant [which one?]. Note that h'...

    1 Answers · Science & Mathematics · 28/02/2020

  8. LHS = xy + xy' = x(y + y') ..........distributive law = x(1) = x RHS = (x+y)(x+y' ) = x+(yy') ...........distributive law = x+(0) .............complement law = x LHS = RHS

    1 Answers · Science & Mathematics · 03/08/2019

  9. ...x = c/d Then x = (c/d) - (a/b) RHS is clearly rational while LHS is irrational. This is a contradiction. Hence the sum must...

    4 Answers · Science & Mathematics · 03/08/2019

  10. ... the given P(t) and showing that it equals the LHS . Or you can find the solution by solving the DE this way: ...

    1 Answers · Science & Mathematics · 14/02/2019

  1. Try asking your question on Yahoo Answers